Effectiveness analysis of a pharmacist-led intervention for orthopedic perioperative use of antibiotics: a retrospective cohort study - Wu, Danwei; Li, Yingxu; Zhen, Jiancun; Wu, Yong; Ren, Shuang; Zhao, Yuan; Sun, Ning; Lin, Xuanzi; Lai, Liangpeng; Zhang, Wei (Frontiers in Pharmacology, 2024)
Background: Following the Chinese guidelines' recommendation to completely cancel routine cephalosporin skin tests, the choice of cephalosporin as surgical prophylactic medication was affected. This was due to the limited cognition of the predictive value of cephalosporin skin test or the desire to avoid medical disputes. The aim of this retrospective study was to evaluate whether the pharmacist-led perioperative antibiotic prophylaxis model could improve clinicians' medical behavior in choosing cephalosporin antibiotics for surgical prophylaxis. Methods: From July 2021 to May 2022, a retrospective analysis was conducted on the selection of surgical preventive medication, skin test, postoperative infection and adverse drug reactions in foot and ankle surgery. The study was divided into three period: the rountine cephalosporin skin test period (Period I: Skin Test), the period when the routine cephalosporin skin test was cancelled but the pharmacist did not intervene (Period II: Skin Test Cancelled), and the period when the pharmacist-led perioperative antibiotic prophylaxis was implemented after the cancellation of the cephalosporin skin test (Period III: Pharmacist Intervention). Results: A total of 1583 patients were enrolled in this study. There was no significant difference in the utilization rate of cefuroxime between the routine skin test stage and the skin test cancelled stage [74.92% (Period I) vs. 74.54% (Period II), P>0.05]. However, in the pharmacist intervention stage, the usage rate of cefuroxime significantly increased compared to the initial stage when the skin test was cancelled [87.07% (Period III) vs. 74.54% (Period II), P<0.05]. The use of cephalosporins also increased in patients with self-reported beta-lactam allergies between these stages [42% (Period III) vs. 3.2% (Period II), P<0.05)]. There was no significant difference in the incidence of postoperative infection and adverse drug reactions among the three periods. Conclusion:The pharmacist-led perioperative antibiotic prophylaxis model can significantly improve the medical behavior of clinicians in choosing cephalosporin antibiotics as surgical prophylactic medication and optimize the perioperative medication plan.